2001
DOI: 10.1001/archinte.161.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Smoking and Weight Control Efforts Among Adults in the United States

Abstract: Adults younger than 30 years are more likely to smoke if they are trying to lose weight. However, smokers of all ages who are trying to lose weight are more likely to want to stop smoking. Patients' weight control efforts should not discourage clinicians from counseling about smoking cessation. Education about smoking and healthy weight control methods should target young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…5,6,17 However, available evidence does not indicate that smoking offers immediate weight control or long-term reduction effects. African-American and white teenagers and young adults [17][18][19] in both cross-sectional and prospective studies have shown no weight control benefit from cigarette smoking.…”
Section: Association Of Smoking and Bmi In Younger Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,17 However, available evidence does not indicate that smoking offers immediate weight control or long-term reduction effects. African-American and white teenagers and young adults [17][18][19] in both cross-sectional and prospective studies have shown no weight control benefit from cigarette smoking.…”
Section: Association Of Smoking and Bmi In Younger Adultsmentioning
confidence: 99%
“…Aside from the addictive properties of nicotine, one possible explanation for the continuation of smoking is the belief that it can assist in controlling body weight. 5,6 An increased awareness of the adverse health effects of obesity and overweight together with peer pressure to encourage slimness may encourage the use of smoking as a means of weight control by young adults. 6 However, the catastrophic increase in health risks when smoking and overweight are combined may not be widely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cessation of smoking without nicotine replacement therapy is usually accompanied by weight gain (Stamford et al, 1986;Levin et al, 1987;Williamson et al, 1991;O'Hara et al, 1998). As a consequence, some people are willing to use smoking in order to lose or maintain their body weight, and are reluctant to stop smoking due to concerns about weight gain on cessation, especially among younger smokers (Crisp et al, 1999;Wee et al, 2001). The effects of cigarette smoking on appetite may also contribute to the morbidity and mortality of smokers with chronic lung disease and wasting.…”
Section: Introductionmentioning
confidence: 99%
“…(French and Jeffery, 1995;Wane et al, 2010) In particular, younger women were more interested in the weight-reducing effects of smoking than older women. (Hjartaker et al, 2001;Wee et al, 2001) Among Asian women, smoking is not only associated with weight control but also with their marital status. According to studies regarding the role of gender in smoking habits, marital status affects smoking behaviors in women to a much greater degree than in men, and marriage plays a greater role as a preventive factor for smoking among women.…”
Section: Introductionmentioning
confidence: 99%